Pemberdayaan Kader Kesehatan Ibu-Ibu Di Lingkungan Monjok Kebon Jaya Barat Melalui Pelatihan Pembuatan Sabun Herbal Daun Kelor (Moringa Oleifera) - Aini, Diah Miftahul; Antari, Gladeva Yugi; Ratnasari, Baiq Desy (Program Studi Pendidikan Kimia FKIP Universitas Mataram, 2024)
Monjok Kebon Jaya Barat, Mataram, has rich natural resource potential, including the Moringa plant (Moringa oleifera) which is known for its skin health benefits. Although the local community has utilised moringa leaves in daily consumption, the great potential for further processing, such as making herbal soap, has not been maximised. Herbal soap made from moringa leaves can be a safer alternative to cleaning products, reduce dependence on harmful chemicals, and support a green economy. This programme aims to empower women health cadres in Monjok Kebon Jaya Barat through skills training in making herbal soap made from moringa leaves. The method used involved three main stages: activity preparation, soap-making training, and sustainability evaluation. In the training, participants were given theoretical and practical knowledge on the benefits of moringa leaves, the saponification process, and herbal soap making. The evaluation showed that most participants were able to follow the training well, although there were some technical constraints related to ingredient measurement and temperature control. The programme had a positive impact on skills enhancement and economic empowerment. The training is effective in introducing herbal soap making and can be a sustainable business opportunity. It is recommended to provide continuous assistance in marketing and the formation of joint business groups to improve the sustainability and welfare of the local community.